Connectivity and Integration of Trading Space: A Space Syntax Study of Pasar Tengah, Bandar Lampung - Mahendra, Fasha Nurliansyah; Putra, Hadi Jaya (Departement of Architecture, Universitas Islam Indonesia, 2024)
Pasar Tengah in Bandar Lampung has evolved as a vibrant trading hub, developing spontaneously and organically over time. Due to the limited availability of land and the use of roads for both social and economic activities, understanding the spatial configuration of this area is crucial for analyzing movement patterns and activity distribution. This study investigates how the spatial configuration of Pasar Tengah influences the distribution and concentration of social and economic activities within the market. Connectivity and spatial integration are key factors shaping the strategic placement of commercial spaces. By employing space syntax analysis and reviewing relevant literature on market activities, the research identifies areas with dominant activity levels based on connectivity and integration metrics. The findings highlight key locations with high activity concentrations, though other factors must also be considered when selecting sites for commercial development. Keywords: Bandar Lampung; connectivity; integration; Pasar Tengah; space syntax